Generator Termoelektrik untuk Pengisisan Aki: Shanti Candra Puspita, Hasto Sunarno, Bachtera Indarto - Shanti Candra Puspita Shanti Candra Puspita; Hasto Sunarno Hasto Sunarno; Bachtera Indarto Bachtera Indarto (Jurnal Fisika dan Aplikasinya, 2017)
Research on termoelectric generator for accu charging has been done to know the effect of different use of sield (heating system framework) between plywood and aluminum on TEG heating system. Besides that also to know how much time needed for charging accu as TEG application. This research is focused on making more efficient heating systems, which is done by increasing the efficiency of the TEG module in generating voltage. In this research, it can be concluded that the update of heating system using Alumunium sield can increase the output voltage of the thermoelectric generator by 4.435% compared to the previous research using TEG type SP184827145SA. While the application of charging Accu using TGPR-1W-2V-21S can produce a voltage of 6 ± 0.05 Volt with a currentof 0.43 ± 0.015 Ampere which requires a duration of charging time of 10 hours.